Sound propagation in liquid He in impurity-helium solids: Low-Temperature Physics and Chemistry in Cryomatrice - Kiselev, S. I.; Khmelenko, V. V.; Lee, D. M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
The observed features of attenuation of ultrasound in Im-He samples created after introduction of impurity particles (D2, N2, Ne, Kr) in a volume of helium II show that a porous substance consisting of a loosely interconnected continuous network is created. It is formed by impurity particles encapsulated in solidified helium. The propagation of ordinary sound in these porous samples is similar to the fastsound mode in light aerogels. The temperature dependence of attenuation for different Im-He samples is investigated. It is established that the character of attenuation in D2-He samples is considerablydifferent from that in heavier Im-He solids (Im = N2, Ne, Kr). Analysis of attenuation lets us conclude that Im-He samples have a wide distribution of pores from 8 nm to 800 nm. The study of ultrasound in helium in Im-He samples near the l-point shows the presence of broadening in the attenuation peak as compared with bulk liquid helium. The suppression of Tc is very small, ≤ 0.2 mK.